Rupture and perforation responses of pressurized tubular members subjected to medium-velocity transverse impact loading. (September 2021) - Zhou, You; Zhang, Shuhua
Highlights: Perforation processes are investigated to reveal the penetration mechanism. Qualitative descriptions are conducted to further understand failure phenomenon. The effects of parameters on perforation depth and stress distribution are studied. Impact limits are obtained over the variation of parameters. Abstract: Rupture and perforation responses of pressurized tubular members subjected to transverse impact loads were systematically analyzed by ANSYS/LS-DYNA. Perforation processes are investigated to reveal the penetration mechanism, including mode transition, transient deformation, velocity variation, energy transfer and stress distribution. Impact limits, including rupture and perforation limit, are studied over the variation of parameters. Effects of various parameters on dimensionless perforation depth, stress distribution and impact limit are discussed respectively. The results show that a variety of failure modes is involved throughout the perforation process, like plugging, flanging and fragmenting. Rupture and perforation limit almost have a linear relationship with the internal pressure and the diameter to thickness ratio. Impact limits increase with impact velocity and internal pressure, and decrease with diameter to thickness ratio. Under the eccentric impact, the penetration form of the pipe performs a tearing pattern rather than completely perforation. The results conclude the perforation depth and impact limits considering significant parameters, which are informative for protection design and damage assessment of pressurized metal tubular members subjected to impact loads.